The new encyclopedia of the opera - Ewen, David, 1907-1985 (Hill and Wang, 1971)
Contains synopses of every major opera and some lesser-known works; biographies of composers, librettists, singers, conductors, impressarios, stage directors, critics, teachers, and musicologists; literary sources of opera; histories of opera houses and festivals; definitions of terms; descriptions of important vocal and instrumental passages.